1999
DOI: 10.1037/0012-1649.35.2.392
|View full text |Cite
|
Sign up to set email alerts
|

"God made me a girl": Sex-category constancy judgments and explanations revisited.

Abstract: To examine reasons for inconsistent findings in the development of sex-category constancy, children's constancy judgments and their accompanying explanations were studied over a 3-year period. Preschool, kindergarten, and 1st-grade children (N = 195) completed a sex-category constancy measure that elicited explanations and assessed constancy for the self and others across changes in gender-typed clothing, activities, and traits. Improvements in sex-category constancy performance were linked to explanations bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
(73 reference statements)
1
43
0
Order By: Relevance
“…One reason is that examining relations in very young children may sometimes be misleading because many young children appear to show a phase of "pseudoconstancy" (Emmerich, Goldman, Kirsh, & Sharabany, 1977;Szkrybalo & Ruble, 1999;Wehren & De Lisi, 1983). Many 3-4-year-olds get all of the answers to a forced-choice gender constancy measure correct, but they do not appear to really understand the constancy of being a boy or a girl.…”
Section: Evaluation Of Gender Constancymentioning
confidence: 99%
“…One reason is that examining relations in very young children may sometimes be misleading because many young children appear to show a phase of "pseudoconstancy" (Emmerich, Goldman, Kirsh, & Sharabany, 1977;Szkrybalo & Ruble, 1999;Wehren & De Lisi, 1983). Many 3-4-year-olds get all of the answers to a forced-choice gender constancy measure correct, but they do not appear to really understand the constancy of being a boy or a girl.…”
Section: Evaluation Of Gender Constancymentioning
confidence: 99%
“…Its development begins at an early stage of human life; research has shown that around the age of 3 years, children show a basic sense of self as male or female 10 , owing to their inner experience of belonging to one gender 11,12 . Furthermore, at 6-7 years of age a child realizes that one's gender is likely to remain constant [13][14][15] . Some research suggests that a developmental lag exists in gender constancy acquisition in children with gender-variant behaviour 16 .…”
mentioning
confidence: 99%
“…Children were given measures of sex typing of themselves and others. A pretest measure of gender constancy was not given, largely because of the concern that the lengthy and unusual line of questioning would prompt children to discuss the topic with authority figures (e.g., parents, teachers) and, as a consequence, would serve to alter children's thinking about gender, as suggested by previous work and pilot testing (Szkrybalo & Ruble, 1999).…”
Section: Overview Of Proceduresmentioning
confidence: 98%
“…Extant studies of constancy have found that different assessments of gender stability and consistency often lead to different conclusions concerning children's understanding of the concept (see Bem, 1989;Emmerich, Goldman, Kirsh, & Sharabany, 1977;Siegel & Robinson, 1987). Most researchers now agree that measures of constancy should (a) contain sets of items designed to assess gender stability and consistency, (b) require children to justify their responses to questions, and (c) avoid the use of unrealistic stimuli such as paper dolls (Bem, 1989;Ruble et al, 2007;Szkrybalo & Ruble, 1999). We use such a measure here.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation